Etnobotani Tumbuhan Obat Suku Melayu Desa Durian Sebatang Kecamatan Seponti Kabupaten Kayong Utara - Riza Linda, Firgian Dine Wulandara Rafdinal (Universitas Tanjungpura, 2018)
This research was conducted with the aim to know the types of medicinal plants, parts of plants used as medicines and methods of processing and the use of plants as a traditional medicine. The research was conducted four months, starting from September to December 2017. The research was conducted in Durian Sebatang Village, Seponti Sub-District, North Kayong District. The research method using Purposive Sampling, with selected respondents as many as 8 people, belong to two categories namely 2 people shaman giving birth and 6 people herbalist. The design of this research is observation, then conducted semi-structured interviews and filling questionnaires by respondents. The results showed that there are 43 families and 93 species of plants that have potential as drugs. The highest percentage of families is Zingiberaceae (9,7%) and Euphorbiaceae (9,7%). Part of a widely used plant is the leaves (48%), while the way of processing and the use of medicinal plants is in boiled (48%) and drunk (53%). Taking medicinal plants is mostly done in the forest (36%).